Analisis Tantangan dan Solusi dalam Pembelajaran Matematika di Era Digital (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study explores the challenges and solutions in mathematics education in the digital era. The rapid development of digital technology has changed teaching methodologies and learning accessibility. This study used a literature review method, analyzing 30 relevant studies from 2021 to 2025. The findings show major challenges such as lack of teacher skills, limited resources, and low digital literacy. In line with this, innovative learning models, infrastructure improvements, and continuous professional development for educators can effectively address these issues. Integrating technology into mathematics education is essential to prepare students for future challenges in an increasingly digital world.